To what extent do climatic stressors drive human mobility in the world’s drylands?: a systematic review of empirical evidence - Link, Ann-Christine; Oakes, Robert; Durand-Delacre, David; Thalheimer-Prezyna, Lisa; Geest, Kees van der (Population and environment, 2025)
Drylands cover a significant portion of the Earth’s surface and support a large share of the global population. They are particularly vulnerable to climate change due to low and highly variable precipitation, changes in precipitation patterns, drought, and desertification. Historically, human mobility has been a critical adaptive response in drylands, supporting communities to cope with climatic and environmental shocks. We use a systematic review of the case study literature in the Web of Science (1976-2023) to assess the effects of climatic stressors on human (im)mobility in drylands. The keywords we use capture various forms of mobility and immobility (migration, displacement, pastoralism, relocation, and immobility) and climatic stressors (rapid-onset, slow-onset, and climate variability) in the world’s 107 countries that have at least 1% of territory classified as drylands. More than nine in ten (91%) of the papers identified climatic stressors as influencing human mobility and immobility, with 76% finding an increase in mobility and involuntary immobility, compared to 15% reporting a decrease in mobility. Migration is the predominant type of mobility assessed by the literature, with droughts and anomalies in precipitation and temperature being the primary climatic stressors. Rapid-onset stressors are more frequently found to increase displacement than slow-onset stressors or climate variability. Climatic stressors tend to have a stronger impact on human mobility in drylands compared to global analyses, which include non-dryland regions. We also show a deficit of empirical studies on pastoralism and immobility, limited research on the effects of compound events on human (im)mobility, and a disproportionate focus of studies on China, the USA, and Mexico, leaving African and South American dryland regions understudied.
Gesehen am 20.01.2026